A Study of Value Trace Problems for Code Reading Study of C Programming - Xiqin, Lu; Funabiki, Nobuo; Sandi Kyaw, Htoo Htoo; Lae Aung, Shune; Dim, Nem Khan (2020 Eighth International Symposium on Computing and Networking Workshops (CANDARW), 2020)
Nowadays, C programming is educated in many universities as the first computer language. It is also essential for studying algorithms and computer architecture. However, a lot of students find difficulty in the study, since it is not familiar to read and understand a C source code. Previously, Java programming learning assistant system (JPLAS) has been developed to assist Java programming study. It offers the value trace problem (VTP) for code reading study. A VTP instance consists of a source code and a set of questions, where each question asks the value of an important variable or the output message in the code. The correctness of an answer is marked through string matching with the correct one. In this paper, we study the value trace problem (VTP) for C programming. 40 VTP instances are generated using source codes for basic grammar concepts, fundamental data structures and algorithms in textbooks or websites. The application results to 25 students using the offline answering function confirm the effectiveness in detecting understanding levels of students and hard problems for them.